Probability Theory and Statistical Inference : Econometric Modeling with Observational Data. - Spanos, Aris (Cambridge University Press, 1999)
This major new textbook is intended for students taking introductory courses in Probability Theory and Statistical Inference. The text is extremely student-friendly, with pathways designed for semester usage, and although aimed primarily at students of econometrics and economics, will have considerable utility for courses in all disciplines using observational data.